The Dynamics of Religion and Ethnic Identity in the Reception of Rohingya Refugees in Aceh - Siregar, Zulfikar Ali Buto; Fithra, Herman; Mukhlis, Mukhlis; Alwi, Said; Iqbal, Muhammad; Haekal, Muhammad (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2024)
This research aims to understand the role of religion as a trigger to the conflict while acting as a social integration to seek a viable, inclusive solution. The research method employed in this study is qualitative, with phenomenology of religion as the approach. The data is collected through observation, interviews, and online media to be classified and analyzed as the discussion and findings. The research found that religious identity creates a discriminatory basis, while religious sentiment worsens the situation, especially when some religious extremists are involved in the conflict. The critical factors in the crisis are the geopolitics of religion, identity formation, communal solidarity, and the global view of the crisis. The Acehnese people saw the refugee crisis as a problem of security and regional stability, human rights, Muslim solidarity, and a geopolitical concern. The involvement of international actors and mass media also contributed to the acceptance issue. This research contributes to understanding the conflict dynamics, Acehnese’s acceptance of the refugees, and its relevance to Southeast Asia politics. The study can also be a reference for more inclusive policy-making in Aceh and Indonesia concerning similar cases.